The user’s perceptions of Perdana Botanical Garden in Kuala Lumpur - Goh, H.C.; Mahmud, N.M. (University of Malaya, 2016)
Public parks are often visualized as open spaces which encourage social interaction and are used for recreational purposes. In Malaysia, the planning of parks is based on the hierarchical planning standard requirement in accordance to the size of catchment area. Public parks at a smaller scale are provided in residential areas for the enjoyment of the neighborhoods. In larger cities such as Kuala Lumpur and Georgetown, urban parks do not only serve as the recreational areas for the residents; they are also tourism attractions, such as Perdana Botanical Garden in Kuala Lumpur, which was originally planned as an urban park in Kuala Lumpur. However, due to the dual uses for both recreation and tourism, conflicts may arise due to the different expectations by park users. This paper intends to reveal the user’s perceptions about the role of Perdana Botanical Garden for recreational purpose. The findings revealed that the park users were satisfied with the activities and facilities offered in the park except the parking facilities especially when its location is not within the walking distance for most of the users. Further to that, it is revealed that the role of Perdana Botanical Garden as a tourism attraction has benefited the park users especially in terms of its management, maintenance and the activities created. Nonetheless, improvement in terms of parking facilities to accommodate the users came with private transportation and better accessibility for the tourists via public transportation mode must be adequately considered.